Science teaching by research: an analysis on production from the ENPEC annals - Bonfim, Ester Angelo; Miranda Junior, Pedro (Revista Hipótese, 2020)
This work presents an analysis of the articles published in the minutes from I to XII ENPEC – National Meeting on Research in Science Education - that focus on teaching science by investigation. It has a qualitative character, with the bibliographic study of articles that were selected by means of keywords. It was observed that research regarding investigative teaching showed growth in the various areas of knowledge and that its inclusion is relevant since the first stage of basic education, as it proposes meaningful and contextualized teaching, placing the student as the protagonist of his learning.
Keywords: Science teaching; Research teaching; ENPEC